Changes in Training, Lifestyle, Psychological and Demographic Factors, and Associations With Running-Related Injuries During COVID-19 - Holmes, Hillary H.; Monaghan, Patrick G.; Strunk, Kamden K.; Paquette, Max R.; Roper, Jaimie A. (Frontiers in Sports and Active Living, 2021)
The primary purpose of this study was to examine how the type and magnitude of changes in running behavior, as a consequence of COVID-19 pandemic restrictions, influence running-related injuries. Secondarily, we aimed to examine how lifestyle and psychosocial well-being measures may influence running behavior change. An online survey was advertised to individuals over the age of 18 that currently run or have previously participated in running for exercise. The survey questions examined injury history and new injuries sustained during COVID-19 restrictions, as well as changes related to training behavior changes, training environment changes, social behaviors, and psychosocial well-being. Changes reflected differences in running behaviors prior to COVID-19 restrictions (1 month prior to COVID-19 restrictions being imposed) and during COVID-19 restrictions (May 5 to June 10, 2020). A total of 1,035 runners were included in the analysis. Current injuries sustained during COVID-19 occurred in 9.5% of the runners. Injured runners made a greater number of total changes (p = 0.031) as well as training-related (p = 0.042) and environment-related (p = 0.017) changes compared with uninjured runners. A significant relationship was found between injury and those that reported less time to exercise to changes in work environment (p = 0017). This study highlights the multi-dimensional nature of running-related injuries and the need to consider the interaction of multiple changes in running behavior, rather than isolating single factors. Greater understanding of the underlying causes of running-related injuries can help reduce the risk of future injury.